Immunopathological Response Of Ducks In aflatoxicosis - Balakrishnan P (Centre of Excellence in Pathology, College of Veterinary and Animal Sciences, 1992)
The immunopathological effects of AFB1 in ducks were studied in this investigation. Both cell – mediated as well as humoral immune system were assessed using suitable immunological markers. White Pekin ducklings were maintained on aflatoxin free feed. AFB1 was administered orally to the 4 week old experimental ducklings at a dose level of 0.075 mg/kg body weight on every alternate day till the end of the experiment. There was reduction in ANAE positive T cells and reduction in the cutaneous response to 2, 4 – dinitrochlorobenzene (DNCB) and phytohaemagglutinin – M (PHA – M) confirming the immunotoxicity of AFB1 on the cell – mediated immune system. The assessment of phagocytic response of reticulo- endothelial cells also indicated a reduced activity in the AFB1 fed ducks. The humoral immune system was evaluated by estimating the total serum protein (TSP), serum globulin (SGI) and various serum immunoglobulin fractions. The AFB1 at the above dose level had significant biological effect on the humoral immune system. It was further confirmed by reduction in the antibody titre in the AFB1 fed ducks vaccinated with RDF1 vaccine. The gross and histopathological features of AFB1 induced toxicity consisted of enlarged, pale and friable liver with haemorrhages, congested kidney with petechial haemorrhages, atrophied spleen, thymus, bursa of Fabricius and caecal tonsils. There was marked histopatological changes in the liver. It being the primary target organ in case of toxicity induced by AFB1. Fatty changes, paracentral and centrilobular necrosis, Proliferation of bile ducts and ductules, severe disorganization of hepatic cords and grouping of hepatocytes with acini – like formations, were seen in the liver. Tubular degeneration and focal necrosis were seen in the kidney. The lymphoid organs like bursa of Fabricius, spleen, thymus and caecal tonsils showed degenerative changes and loss of lymphoid elements. There were loss of follicular pattern with interstitial fibrosis and necrobiotic changes in lymphoid elements in the bursa of Fabricius. The thymus revealed atrophy, necrosis, interstitial edema and intense lympholytic changes. Caecal tonsils revealed haemorrhages, degeneration of lymphoid cells and necrosis. In this investigation the immunosuppressive effects of AFB1 on the humoral and cell – mediated immune system of ducks were evaluated. Regular screening of feed for AFB1 was advocated as a routine farm practice to prevent the deleterious effect of AFB1 on the health and productivity of ducks.